Design of Instrument Control System Based on LabVIEW - Jiang Chao; Xu Wu-bin; Li Bing (Institute of Advanced Engineering and Science, 2013)
In order to solve the problems such as poor expansion, long development cycle of instrument control system developed by traditional programming language, using VISA module based on LabVIEW platform was introduced. This paper presented a simplicity, intuitive instrument control system of pneumatic measuring instrument, which was accomplished with graphical language LabVIEW. The system could also complete the text data output. It was improved that the system based on LabVIEW achieved instrument control efficiently, openly, with operating conveniently and good human-machine interface. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2719